2003
DOI: 10.1051/rnd:2003016
|View full text |Cite
|
Sign up to set email alerts
|

Use of some novel alternative electron sinks to inhibit ruminal methanogenesis

Abstract: -Several compounds were evaluated in vitro as alternative electron sinks to ruminal methanogenesis. They were incubated with ruminal fluid, buffer mixture, and finely ground alfalfa hay for 24 h, at 0, 6, 12, and 18 mM initial concentrations. The propionate enhancer oxaloacetic acid, the butyrate enhancer β-hydroxybutyrate, and the butyrate unsaturated analog 3-butenoic acid were ineffective in decreasing methanogenesis. Nevertheless, β-hydroxybutyrate increased apparent fermentation of the alfalfa hay substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 28 publications
9
47
1
Order By: Relevance
“…Finally, ethanol concentrations increased with NIT supporting the hypothesis that this alcohol may have a role in disposing reducing equivalents spared from methanogenesis (Ungerfeld et al, 2003). Overall, NIT stimulated [2H] producing pathways as shown by the greater acetate molar percentage.…”
Section: Discussionsupporting
confidence: 62%
“…Finally, ethanol concentrations increased with NIT supporting the hypothesis that this alcohol may have a role in disposing reducing equivalents spared from methanogenesis (Ungerfeld et al, 2003). Overall, NIT stimulated [2H] producing pathways as shown by the greater acetate molar percentage.…”
Section: Discussionsupporting
confidence: 62%
“…It is presumably that the methane-suppressing effects of TS may lead to accumulations of hydrogen (Hu et al, 2005). Another way of diverting hydrogen away from methane formation would be to promote alternative electron-sink metabolic pathways to dispose of the reducing power (Ungerfeld et al, 2003), and fumarate has been shown to compete successfully for hydrogen (Newbold et al, 2005). However, further addition of DF did not have better inhibitory effects on methane emissions compared to TS addition only.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in CH 4 production usually occur with an alteration in the VFA profile because of alternative electron sinks to dispose of reducing power. Moreover, the transformation of the feed to propionate usually limits the rate of methanogenesis due to the impact of hydrogen transfer (Ungerfeld et al, 2003). The supplementation with sage increased propionate and total VFA concentrations and also altered the A:P ratio, simultaneously inhibiting digestibility in vitro.…”
Section: Discussionmentioning
confidence: 99%